Respuesta :
Hello from MrBillDoesMath!
Answer:
(x+2) ( x^2 + 3)
Discussion:
x^3 + 2x^2 + 3x + 6 =
( x^3 + 2x^2) + (3x + 6) = => factor "x^2" from the first term; factor 3
from the second term
x^2( x + 2) + 3( x+2) = => factor (x+2) from each term
(x+2) ( x^2 + 3)
Thank you,
MrB
Answer:
(x+2)(x²+3)
Step-by-step explanation:
We have given an expression.
x³+2x²+3x+6
We have to factor by using grouping method.
Making two groups of two terms that has any common factor, we have
(x³+2x²)+(3x+6)
Since x² is common factor in first parentheses and 3 is common in second parentheses.
taking common, we have
x²(x+2)+3(x+2)
Taking x+2 as common, we have
(x+2)(x²+3)
Hence, x³+2x²+3x+6 has two factors (x+2) and (x²+3).